2018
DOI: 10.13181/mji.v27i2.2413
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge retention after continuing health education among midwives in Indonesia

Abstract: Background: Amongst the Health Care Professionals, midwife has a strategic role in taking care of both mother and child in contributing to their survival, health, and wellbeing. The retaining midwife’s knowledge and quality of care through training on specific skills is strongly needed. This study aimed to evaluate the knowledge retention among midwives after the provision of digestive health, nutrition, and parenting education sessions at immediate and three months after the education.Methods: A serial pre-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…Our study showed a decrease in knowledge scores compared to the first follow-up. These findings are like another study where there was a decline in knowledge in the three-month follow-up group compared to the immediate group [ 34 ]. Although knowledge can decrease with time, it is important to maintain healthy beliefs and practice behaviors.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed a decrease in knowledge scores compared to the first follow-up. These findings are like another study where there was a decline in knowledge in the three-month follow-up group compared to the immediate group [ 34 ]. Although knowledge can decrease with time, it is important to maintain healthy beliefs and practice behaviors.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it must be reevaluated after the training is done. It is done to ensure that good quality health services can still be provided by health workers, especially related to anemia management, so that this condition can be prevented earlier [ 27 ]. The training provided must also be able to run effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge competency as well as updated education program should also need to be considered in future research, as study showed that retaining medical staff's knowledge and quality of care through training on specific skills is strongly needed and potentially influence the skill and competency. 27,28 It is important to conduct better structured survey with bigger sample size to identify the in-depth perspective, understanding and knowledge of Indonesian pediatricians toward Csection and its impact to long-term health.…”
Section: Discussionmentioning
confidence: 99%